Improving the thermal processing of foods - Richardson, P. (Woodhead Publishing in food science and technology., 2004)
The application of heat is both an important method of preserving foods and a means of developing texture, flavour and colour. It has long been recognised that thermal technologies must ensure the safety of food without compromising food quality. Improving the thermal processing of foods summarises key research both on improving particular thermal processing techniques and measuring their effectiveness. Part one examines how best to optimise thermal processes, with chapters addressing safety and quality, efficiency and productivity and the application of computational fluid dynamics. Part two focuses on developments in technologies for sterilisation and pasteurisation with chapters on modelling retort temperature control and developments in packaging, sous-vide and cook-chill processing. There are chapters covering continuous heat processing, including developments in tubular heat exchangers, aseptic processing and ohmic and air impingement heating. The fourth part considers the validation of thermal processes, modelling heat penetration curves, using data loggers and time-temperature integrators and other new measuring techniques. The final group of chapters detail methods of analysing microbial inactivation in thermal processing and identifying and dealing with heat-resistant bacteria. Improving the thermal processing of foods is a standard reference book for those working in the food processing industry. Concisely explores prevailing developments in thermal technologiesSummarises key research for improving food preservation techniquesAnalyses the effectiveness of methods used to enhance the quality of food.